Productivity Analysis of German Electricity Distribution Utilities - Christian R. von Hirschhausen; Andreas Kappeler (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
The paper is the first productivity analysis of a large number of German electricity distributors to date. In it, we address both traditional issues of electricity sector benchmarking, such as the role of scale effects and optimal utility size, as well as new evidence specific to the situation in Germany. Regarding the latter, we consider the potential effects of three structural variables: consumer density, grid composition (cable versus aerial lines), and differences between East and West German distribution companies. Our empirical section thus follows the structural criteria set out by the German association agreements (?Verbändevereinbarung Strom VV II+?). The data covers 380 (out of 553) German electricity distribution utilities.
Keywords: 330; Elektrizitätswirtschaft; Energieverbund; Produktivität; Schätzung; Deutschland